Revised Ordinances of the City of Woburn 91 (1898) - (:unkn) unknown (My University, 1898)
§§ 2-4: No person shall sell any gunpowder within the city, without such license. Every license shall be in force one year from the date thereof; provided, that any license may be rescinded by the City Council, at their discretion.§
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER